IMPLEMENTASI LESSON STUDY SEBAGAI UPAYA UNTUK MENINGKATKAN HASIL BELAJAR DALAM PERKULIAHAN MATEMATIKA DISKRIT - Vera Dewi Kartini Ompusunggu; Nilam Sari (JURNAL CURERE, 2021)
This study aims to reveal how the implementation of lesson study in Discrete Mathematics lectures in mathematics education study program in class 2A41 class 2016 Universitas Quality. The method used in this research is descriptive analytic method with a qualitative approach. The research subjects in this study consisted of 1 model lecturer, 3 observers, 1 facilitator and 18 students of class 2A41 class 2016 at the University of Quality who took discrete mathematics courses. Data collection techniques used in this study were interviews, observation and documentation study. The implementation of open lessons in discrete mathematics courses on the subject of set definition, set operations, Cartesian product, set laws to the principle of duality with a problem posing approach is carried out in three cycles. The stages of planning (Plan), Implementation (Do), and Reflection (See) have been carried out properly according to the lesson study guidelines.